ETFs Volatility Spillover on South-East Asian Equity Markets with Intraday and Daily Empirical Evidence - Rawat, Sundas (2015)
This study investigates the volatility spillover of three SouthEast Asian Exchange Traded Funds on their stock indices. The ETFs chosen for the purpose of this study are; MVV VNM ETF which tracks the Market Vectors Vietnam ETF Stock Index, EPHE ETF which tracks the iShares MSCI Philippines ETF, EIDO ETF iShares MSCI Indonesia ETF. This study has used 5 minute intraday data on ETFs and stock indices to examine the volatility change that has taken place due to the introduction of the ETFs. The GARCH (1,1) test has been used by this study to check whether the introduction of the ETFs led to a change in the volatility of the stocks or not. The Andersen test has been used by this study to check whether there had been an increase in the volatility of the Stock Indices due to the introduction of the ETFs. This study has also used the Diebold and Yilmaz Model with daily data on the ETFs and their ten largest component stocks to check whether there is still a volatility spillover now in the chosen markets, and the direction of the volatility. The results show that the introduction of ETFs changed the volatility of all the chosen Equity Markets. However, the volatility only increased significantly in Indonesia. Moreover, this study has also shown that there is currently a bi-directional volatility spillover between ETFs and their component stocks, but the spillover is much stronger from ETFs to their stocks. Hence, the VNM, EIDO and EPHE ETFs transmit volatility to the stock market in general, by transmitting volatility to their largest component stocks.